The Effects of Husband Support, Motivation, and Self-Efficacy on the Examination of Visual Inspection of Acetic Acid (IVA) in Karawang Village, Karawang Health Center, and Sukabumi Regency in Women of Childbearing Age (PUS) - Haryani, Hana (STIKep PPNI Jawa Barat, 2022)
Aims: Cervical cancer can be prevented with vaccination and early detection, which can halt the progression of the disease. The IVA test is one of the most effective cervical cancer screening procedures available. Several factors influence IVA examination target attainment, including husband support, motivation, and self-efficacy in the IVA examination. The goal of this study was to discover what factors influence the visual inspection of acetic acid by women of childbearing age (PUS) (IVA). Methods: This is a cross-sectional approach to correlational research. With a sample size of 318 people, the population is all women of childbearing age (PUS) in Karawang Village, Karawang Working Area of Karawang Health Center, Sukabumi Regency. Cluster random sampling is used for sampling. Questionnaires were used to collect data, and Chi-square was used for statistical analysis. Results: The findings revealed that husband support influenced the visual inspection of acetic acid (IVA) (p-value 0.001), there was no motivational influence on the visual inspection of acetic acid (IVA) (p-value 0.218), and there was no effect of self-efficacy on the visual inspection examination of acetic acid (IVA) (p-value 0.393). Conclusions: The visual inspection of acetic acid (IVA) in women of childbearing age (PUS) partners is influenced by husband support.